ІНСТИТУЦІЙНЕ СЕРЕДОВИЩЕ МУЛЬТИМОДАЛЬНИХ (ЗМІШАНИХ) ПЕРЕВЕЗЕНЬ ЗА УЧАСТЮ ЗАЛІЗНИЧНОГО ТРАНСПОРТУ: ЄС ТА УКРАЇНА (International Journal of Innovative Technologies in Economy, 2018)
The institutional environment of multimodal (mixed) transport with the participation of rail is considered. The analysis of the main provisions of formal institutes regulating multimodal transportations at the international, European and national levels was carried out. As a result, it was determined: 1) at the international level, there is no single universal and legally defined concept of "multimodal transportation"; 2) the concept of "multimodal transportation" is defined as the basis in the mixed transport of goods, which includes intermodal, which in turn include the combined, serving their subspecies; 3) measures to stimulate the development of multimodal (mixed) transport with the participation of rail in Ukraine are proposed. They relate to improving the institutional environment (formal institutions) implementation of multimodal (mixed) transportation.